The Eyes Test as a Measure of Individual Differences: How much of the Variance Reflects Verbal IQ? - Peterson, Eric; Miller, Stephanie (Frontiers in Psychology, 2012)
Developed by Baron-Cohen and colleagues, the Reading the Mind in the Eyes Test requires individuals to determine mental states from photos of pairs of eyes. Used in over 250 studies, it has been conceptualized as an advanced theory of mind test that is relatively free of general cognitive abilities. Given the sensitivity of the instrument, many studies with healthy adult samples have used this instrument as a measure of individual differences in social perceptual processes that contribute to theory of mind and overall phenotype. We administered the two-subtest WASI, a face processing task (Cambridge Face Memory Test), and the Eyes Test to forty-two college students. Surprisingly, verbal IQ contributed significantly to the variance in Eyes Test performance while the face perception measure did not. These findings have both practical and theoretical ramifications for interpreting Eyes Test results in normative adult samples.